Reporting doping in sport: National level athletes' perceptions of their role in doping prevention. Issue 6 (27th March 2014) - Whitaker, L.; Backhouse, S. H.; Long, J.
<x xml:space="preserve">Abstract</x> This paper qualitatively explores national level athletes' willingness to report doping in sport. Following ethical approval, semi‐structured interviews were conducted with nine national level athletes from rugby league (n = 5) and track and field athletics (n = 4). Thematic analysis established the main themes within the data. Contextual differences existed around the role that athletes perceived they would play if they became aware of doping. Specifically, track and field athletes would adopt the role of a whistle‐blower and report individuals who were doping in their sport. In comparison, the rugby league players highlighted a moral dilemma. Despite disagreeing with their teammates' actions, the players would adhere to a code of silence and refrain from reporting doping. Taking these findings into account, prevention programs might focus on changing broader group and community norms around doping. In doing so, community members' receptivity to prevention messages may increase. Moreover, developing skills to intervene (e.g., speaking out against social norms that support doping behavior) or increasing awareness of reporting lines could enhance community responsibility for doping prevention. In sum, the findings highlight the need to consider the context of sport and emphasize that a one‐size‐fits‐all approach to anti‐doping is problematic.